Law Compliance, and Prevention and Control of Illegal Activities in the Forest Sector in Suriname : Country Assessment - Playfair, Maureen (World Bank, Washington, DC, 2021)
Suriname is situated on the northeast coast of South America, and with a land area of just 16.4 million hectares, is one of the smallest countries on the continent. The population totals 480,000, with nearly 70 percent living in the capital city. Paramaribo and the surrounding district. Meanwhile, a quarter of the population lives in smaller settlements along the coast and about 70,000 people from tribal maroon.